MEMBANGUN SISTEM KEUANGAN YANG KOKOH DAN PEMASARAN KREATIF UNTUK UMKM TELOR ASIN DI DESA CIBUAH KECAMATAN WARUNGGUNUNG, KABUPATEN LEBAK - Kartika, Rika; Budiman, Dedi; Hidayatullah, Rizki; Basayev, Gito Syamil; Muiz, Ahmad (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
The community service activity with the theme "Building a Strong Financial System and Creative Marketing for Salted Egg MSMEs in Cibuah Village, Warunggunung District, Lebak Regency" aims to improve financial management and marketing skills for MSMEs in the village. This activity includes thorough preparation, an initial welcome, as well as in-depth training sessions on financial recording and digital marketing. Participants are trained in the use of a simple ledger, practical bookkeeping techniques, and digital marketing strategies, including product photography. The final evaluation showed that participants gained significant benefits and were ready to apply new knowledge to their business. This program succeeded in building a solid foundation for financial management and expanding the market reach of MSMEs, as well as providing valuable feedback for future program development